A articulação do quadril em uma perspectiva preditora da velocidade de marcha em idosas e como foco de intervenção de duas modalidades terapêuticas: Método Pilates e Haste Vibratória - Gotardo, Mary Hellen Morcelli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Lower muscle strength of hip, knee and ankle has been related to slow gait speed. Thus, the muscle strength is considered a critical musculoskeletal component for functional independence in elderly and to determine which joint of lower limb is the best predictor of gait speed in the elderly is clinically relevant. Moreover, it is important to study if specific muscular strength protocols, such as Pilates and vibratory pole, are effective in the improvement of neuromuscular capabilities of better joint to predict gait speed. Objective: Determine which joint of the lower limb is the best predictor of gait speed in elderly, to determine thresholds of strength for normal gait speed and investigate whether the Pilates and vibratory pole training improve the torque an power muscle, rate of torque development and neuromuscle activation of better joint to predict gait speed in the elderly, besides evaluating the influence of both training on the kinematics of the gait in older women. Methods: Aged 60-85 years participated in this study. It was initially performed the assessment of muscle strength the three joints of the lower limb (hip, knee and ankle) in the sagital plane in a isokinetic dynamometer synchronized with electromyography of the lower limbs. Moreover, the kinematics gait parameters on treadmill were determined using a seven-camera system. After the initial assessment, older women were divided into two groups, and each group has undergone specific training for 8 weeks. The training were: Pilates (n=19) and vibratory pole (n=18). After the 8-week of training the older women were reassessed. The effect of training was observed for the following biomechanical variables: rate of torque development, torque and muscle power of the hip flexion and hip extension, activation of the rectus femoris, biceps femoris, gluteus maximus, internal oblique and multifidus. With respect to kinematic analysis it was observed the ...

Introdução: A redução na força dos músculos que envolvem a articulação do quadril, joelho e tornozelo tem sido associada a baixa velocidade de marcha. Desta forma, a força muscular é considerada um componente musculoesquelético crucial para independência funcional em idosos. Assim, a determinação de qual articulação do membro inferior é a melhor preditora da velocidade de marcha em idosos é clinicamente relevante. Tendo determinado a articulação preditora da velocidade de marcha, faz-se necessário verificar se protocolos de treinamento de força muscular são eficazes no aprimoramento das capacidades neuromusculares dessa articulação, como por exemplo, treinamento com método Pilates e haste vibratória. Objetivo: Assim, este trabalho objetivou determinar qual grupo muscular do membro inferior é o melhor preditor da velocidade de marcha em idosos, estabelecer limiares de força muscular para velocidades funcionais da marcha e investigar se o treinamento com método Pilates e com haste vibratória são capazes de aumentar o torque e potência muscular, a taxa de desenvolvimento de força (TDF) e a ativação muscular da articulação do membro inferior que melhor determina a velocidade de marcha, bem como avaliar a influência de ambos treinamentos na cinemática da marcha de idosas. Métodos: Idosas entre 60-85 anos participaram do presente estudo, sendo que no primeiro momento foi realizada a avaliação da força muscular das três articulações do membro inferior (quadril, joelho e tornozelo) no plano sagital, utilizando um dinamômetro isocinético sincronizado a eletromiografia dos membros inferiores. Além disso, também foi analisada a cinemática da marcha em esteira ergométrica através de um sistema de sete câmeras. Após a avaliação inicial, as idosas foram dividas em dois grupos e cada grupo foi submetido a um treinamento específico durante 8 semanas. Os treinamento realizados foram: Método Pilates...
Keywords: Aging; Envelhecimento; Aptidão física; Marcha humana; Idoso; Quadril; Membros inferiores; Pilates, Método